2017
DOI: 10.1149/2.0581704jes
|View full text |Cite
|
Sign up to set email alerts
|

Sensitive Anodic Stripping Voltammetric Determination of Indium(III) Traces Following Double Deposition and Stripping Steps

Abstract: A procedure for the determination of In(III) by anodic stripping voltammetry following double deposition and stripping steps was described. Two environmentally friendly electrodes with different surface areas -glassy carbon macroelectrode and an ensemble of carbon composite microelectrodes -modified with bismuth films were used for the measurements. Parameters affected In(III) determination were optimized. Under optimized conditions the calibration graph was linear from 5 × 10 −10 to 2 × 10 −8 mol L −1 followi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
16
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 33 publications
(37 reference statements)
0
16
0
Order By: Relevance
“…Furthermore, using microelectrodes leads in many cases to favorable signal to noise ratio [35]. For the construction of microelectrodes metallic electrode materi-als [36][37][38][39][40] as well as various carbon materials and composites were utilized [41][42][43][44] and many different geometries of microelectrodes were proposed [45].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, using microelectrodes leads in many cases to favorable signal to noise ratio [35]. For the construction of microelectrodes metallic electrode materi-als [36][37][38][39][40] as well as various carbon materials and composites were utilized [41][42][43][44] and many different geometries of microelectrodes were proposed [45].…”
Section: Introductionmentioning
confidence: 99%
“…Electroanalytical sensors offer great opportunities to quantify the total indium amount at micromolar concentrations levels, using ex-situ plated antimony film [18][19][20] or bismuth film [21] electrodes. Another study reported the analytical performance of the adsorptive stripping electrochemical techniques (AdSV) in terms of linear ranges of calibration and limits of detection [22].…”
Section: Introductionmentioning
confidence: 99%
“…The subject of this article is reviewing the results of research concerning the utilization of double deposition/ accumulation and stripping steps as a new way of lowering the detection limit and increase the selectivity of determination of selected ions: (Pb(II), Cd(II), Tl(I), U-(VI), Au(III), As(III), Se(IV), In(III), Co(II), Cu(II), Bi-(III) and Ga(III)) [39][40][41][42][43][44][45][46][47][48][49]. A significant decrease of the detection limits of the procedures of inorganic ions determination discussed below was obtained by omitting the additional step of preconcentration of the analyte outside the electrochemical cell before a proper analysis with the use of the environmentally friendly electrodes (or more environmentally friendly as compared to mercury ones).…”
Section: Introductionmentioning
confidence: 99%
“…In paper [25] an idea of double deposition and stripping steps similar to the abovementioned procedures [39][40][41][42][43][44][45][46][47][48][49] was utilized for Pb(II) and Cd(II) determination, however, in the mentioned protocol after the first deposition step a polarization of the first electrode was interrupted and then this electrode was quickly transferred to the another electrolytic cell of smaller sizes. During this transfer, the deposited metals had a contact with atmospheric air that might have resulted in a partial oxidation of deposited species.…”
Section: Introductionmentioning
confidence: 99%